1998
DOI: 10.1046/j.1432-1327.1998.2540096.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbon‐flux distribution in the central metabolic pathways of Corynebacterium glutamicum during growth on fructose

Abstract: Growth of Corynebacterium glutamicum on fructose was significantly less than that obtained on glucose, despite similar rates of substrate uptake. This was in part due to the production of overflow metabolites (dihydroxyacetone and lactate) but also to the increased production of CO 2 during growth on fructose. These differences in carbon-metabolite accumulation are indicative of a different pattern of carbon-flux distribution through the central metabolic pathways. Growth on glucose has been previously shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
128
1
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(139 citation statements)
references
References 7 publications
8
128
1
1
Order By: Relevance
“…Carbon flux analysis revealed that during growth on glucose, NADPH for lysine biosynthesis is provided by the PPP, whereas isocitrate dehydrogenase and malic enzyme are of minor importance (Marx et al 1996(Marx et al , 1997(Marx et al , 1999. During growth of C. glutamicum on fructose or on fructose/glucose mixtures, a low carbon flux through the oxidative PPP was demonstrated (Dominguez et al 1998;Kiefer et al 2004;Pons et al 1996). It was proposed that to meet the NADPH requirement for growth and lysine production on fructose or on fructose/glucose mixtures, malic enzyme activity has to be increased (Dominguez et al 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon flux analysis revealed that during growth on glucose, NADPH for lysine biosynthesis is provided by the PPP, whereas isocitrate dehydrogenase and malic enzyme are of minor importance (Marx et al 1996(Marx et al , 1997(Marx et al , 1999. During growth of C. glutamicum on fructose or on fructose/glucose mixtures, a low carbon flux through the oxidative PPP was demonstrated (Dominguez et al 1998;Kiefer et al 2004;Pons et al 1996). It was proposed that to meet the NADPH requirement for growth and lysine production on fructose or on fructose/glucose mixtures, malic enzyme activity has to be increased (Dominguez et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…During growth of C. glutamicum on fructose or on fructose/glucose mixtures, a low carbon flux through the oxidative PPP was demonstrated (Dominguez et al 1998;Kiefer et al 2004;Pons et al 1996). It was proposed that to meet the NADPH requirement for growth and lysine production on fructose or on fructose/glucose mixtures, malic enzyme activity has to be increased (Dominguez et al 1998). As fructose is transported into the cell as fructose-1-phosphate by a PEP-dependent phosphotransferase system and enters glycolysis after phosphorylation to fructose-1,6-bisphosphate (Kotrba et al 2001;Parche et al 2001), overexpression of the fructose-1,6-bisphosphatase gene fbp (Rittmann et al 2003) was alternatively proposed to increase the PPP flux as well as lysine production on fructose (Kiefer et al 2004;Pons et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The role of malic enzyme is still not completely clear. Its contribution to NADPH supply has been demonstrated for growth on fructose [32] as well as in a pyruvate kinase deficient lysine production strain [120]. Lysine production flux (%) Fig.…”
Section: Metabolic Fluxes Of Nadph Metabolismmentioning
confidence: 95%
“…The major enzymes are glucose 6-phosphate dehydrogenase [28,29] and 6-phosphogluconate dehydrogenase [28,30] in the oxidative part of the PPP and the TCA cycle enzyme isocitrate dehydrogenase [31]. In selected cases, NADPH supply might involve malic enzyme [32,33]. In addition to the central catabolism, anabolic routes have also been elucidated.…”
Section: Central Carbon Metabolismmentioning
confidence: 99%
See 1 more Smart Citation